Rosario López Gregoris y Cristóbal Macías Villalobos (coords.), The Hero Reloaded. The reinvention of the classical hero in contemporary mass media, Amsterdam / Philadelphia, 2020 (Carolina Real Torres) - Real Torres, Carolina (Revista de Estudios Latinos, 2020)
Rosario López Gregoris y Cristóbal Macías Villalobos (coords.), The Hero Reloaded. The reinvention of the classical hero in contemporary mass media, Amsterdam / Philadelphia, John Benjamins Publishing Company, 2020, 160 + XIV pp. ISBN: 978-90-272-0495-0 ; 978-90-272-6155-7.